2021
DOI: 10.1590/1980-220x-reeusp-2020-0084
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of evaluations performed by undergraduate nursing alumni: a Brazilian multicenter study

Abstract: Objective: To compare evaluations performed by undergraduate nursing alumni in three dimensions: sociodemographic characterization, identification and insertion into the job market, and professional training evaluation. Methods: Cross-sectional, quantitative, and multicenter study with alumni of three Brazilian public institutions. Data analysis was carried out according to the internal reliability of the used instrument and by applying descriptive statistics. Results: The participants were 446 alumni who ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(41 reference statements)
1
1
0
2
Order By: Relevance
“…This underscores the importance of including a discussion of gender in nursing education (10) . This study observed the presence of increasingly younger nursing students, with graduates identified at approximately 21 years of age, a recurring finding in the literature (11)(12) . This reflects the rejuvenation of the field, due to factors such as policies to promote higher education in Brazil and the importance placed on financial independence and delaying marital commitments, reinforced by the predominantly unmarried and employed sample of this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This underscores the importance of including a discussion of gender in nursing education (10) . This study observed the presence of increasingly younger nursing students, with graduates identified at approximately 21 years of age, a recurring finding in the literature (11)(12) . This reflects the rejuvenation of the field, due to factors such as policies to promote higher education in Brazil and the importance placed on financial independence and delaying marital commitments, reinforced by the predominantly unmarried and employed sample of this study.…”
Section: Discussionsupporting
confidence: 58%
“…This reinforces the view that the psychosocial impact on a population exposed to the pandemic can be multifaceted (2,6,10,(17)(18)(19) . In addition, negative strategies, alcohol, and tobacco use among university students have been identified in other studies (10)(11)(12)(13)(14)(15) and appear to be common due to their legality, social acceptance, promotion of sociability and relaxation. One study found that alcohol and tobacco use was higher among older students, with physical activity serving as a protective factor against such use.…”
Section: Discussionmentioning
confidence: 94%
“…O seguinte estudo apresentou dados semelhantes concernentes ao gênero (Figura 1), 88,6% do sexo feminino e 11,4% do sexo masculino. Referente à idade, os dados foram divergentes (Figura 2), evidenciados pela predominância da faixa etária de 26 a 30 anos, totalizando 46,9% dos entrevistados Vieira & De Domenico, 2021). Buscando verificar o conhecimento dos acadêmicos sobre as fases do parto vaginal (Figura 4), mostrou que 75,8% (n= 50) responderam sim, e 24,2% (n=16) não compreendem as etapas do parto vaginal.…”
Section: Resultsunclassified
“…Quanto ao perfil dos participantes foi composto por população jovem de até 25 anos, divergente de estudo multicêntrico brasileiro com egressos em que 46,9% dos participantes tinham entre 26 e 30 anos. (11) Majoritariamente eram do sexo feminino e autodeclaradas brancas, correspondente ao perfil da enfermagem brasileira identificado em pesquisa nacional. (12) Percentual significativo de enfermeiros pretos e pardos foi encontrado nesta pesquisa, que pode ser decorrente das políticas afirmativas instituídas no Brasil.…”
Section: Discussionunclassified